THE IMPLEMENTATION OF THE PICTURE-BASED STORYTELLING METHOD TO IMPROVE STUDENTS’ SPEAKING SKILL - Nurhafid, Alif Majid; Purwanto, Buntara Adi (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2024)
This research study aimed to develop students' speaking skills in english at MTs Ma'arif Sojokerto which is located in Leksono Village, Wonosobo Regency. The researcher was given this opportunity by the headmaster to visit and observe the school to identify the problems related to this study. The researcher used the Picture-based Storytelling method to overcome students' problems in speaking english by using classroom action research design (CAR). This research consisted of 2 cycles, which each cycle has stages namely planning, implementing, observing and reflecting. The sample taken for this study was class VIII at that school. The research instrument had several parts, namely interviews, observations, test results and documentation. The results of observations, and tests increased. The results of the observation, in the pre-cycle amounted to 30%, in cycle 1 amounted to 52% and in cycle 2 amounted to 84%. Then, the results of the test, in the pre-cycle, amounted to 29%, in cycle 1, it amounted to 50% and in cycle 2, it amounted to 75%. The results of the interview test also changed, from the previous class action research conducted, students did not like English lessons to liked English lessons after using this method. From the results obtained by the researcher, it can be concluded that the use of the Picture-based Storytelling method can improve students in speaking english.